Flavonoids fractions of Adansonia digitata L. fruits protects adult Wistar rats from mercury chloride-induced hepatorenal toxicity: histopathological and biochemical studies. Issue 1 (31st December 2022) - Makena, Wusa; Aribiyun, Yomi Samson; Aminu, Aisha; Ishaku, Barka; Yohana, Ayuba; Inemesit, Ekwere Eke
ABSTRACT: Mercury chloride is a common heavy metal found in the environment, and it endangers both the environment and living organisms. The study aimed to show whether Flavonoids Fractions of Adansonia digitata (FAD) could protect rats from HgCl2 -induced hepatorena toxicity. Thirty (30) rats were randomly assigned to one of six groups. The first group was given no HgCl2 as a control, while the second group was given a single daily dose of HgCl2 (0.5 mg/kg). The treatment groups (III, IV, and V) received a single daily dose of HgCl2 (0.5 mg/kg) along with 25 mg/kg, 50 mg/kg, and 75 mg/kg of FAD, respectively. HgCl2 (0.5 mg/kg) was given to Group VI, along with Ascorbic Acid (200 mg/kg) as a standard control. After the administration, the blood serum of the experimental rats was used for biochemical analysis. The liver and kidney organs were obtained for histological examination. AST, ALP, ALT, urea, creatinine, and MDA levels all increased in rats given HgCl2 (group II), with decreased SOD, CAT, and GSH levels (p < 0.001), whereas FAD was able to prevent the upsurge of ALT, AST, ALP, creatinine, Urea, and MDA. It also increased SOD, CAT, and GSH levels in the body. FAD protected the glomerulus from degeneration and prevented histological liver steatosis.